Endometriosis: An Immunologist's Perspective - Garmendia, Jenny Valentina; De Sanctis, Claudia Valentina; Hajdúch, Marian; De Sanctis, Juan Bautista (International journal of molecular sciences, 2025)
Endometriosis, a complex inflammatory disease, affects a significant proportion of women of reproductive age, approximately 10-15%. The disease involves the growth of endometrial glands and stroma outside the uterine cavity, leading to tissue remodeling and fibrosis. Hormonal imbalances, accompanied by local and general inflammation and pain, are key features of endometriosis. Endometriotic lesions are associated with the overproduction of cytokines, metalloproteinases, prostaglandins, reactive oxygen radicals, and extracellular vesicles. Genetic predisposition and cytokine gene polymorphisms have been documented. Macrophages, dendritic cells, mast cells, Th1 in the early phase, Th2 in the late phase, and T regulatory cells play a crucial role in endometriosis. Reduced NK cell function and impaired immune vigilance contribute to endometrial growth. The strong inflammatory condition of the endometrium poses a barrier to the proper implantation of the zygote, contributing to the infertility of these patients. Cytokines from various cell types vary with the severity of the disease. The role of microbiota in endometriosis is still under study. Endometriosis is associated with autoimmunity and ovarian cancer. Hormonal treatments and surgery are commonly used; however, recent interest focuses on anti-inflammatory and immunomodulatory therapies, including cytokine and anti-cytokine antibodies. Modulating the immune response has proven critical; however, more research is needed to optimize treatment for these patients.
Keywords: endometriosis; endometrium; cytokiny; Female; therapy; inflammation; Endometriosis; Animals; Humans; ženské pohlaví; cancer; autoimmunity; lidé; endometrióza; cytokines; zvířata; Endometrium; Cytokines